Del testimonio a la memoria: el a posteriori entre la historia y las ruinas (2012)
Based on library research this paper analyzes the relations between testimony and memory according to Giorgio Agamben, Sigmund Freud and Walter Benjamin. In such authors, it turns out that the notions of forgetfulness, rest, ruins and a posteriori are present in the discourse on testimony and memory. It elaborates the synergy found in the studies by these authors, which stress the possibilities of displacement of subjective positions during the memory task. In this context, the incompleteness of history takes prominence, allowing the recovery of the past and its meanings. Now that that Brazil is putting the spotlight on its Truth Commission, an open discussion of the revisited past emphasizes the importance that we understand the limits of the expression of memory provided by the testimony.